Coach and biomechanist knowledge of sprint running technique - Amy, W.; Phillips, E.; Panchuk, D.; Dawson, A. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to establish how coaches and biomechanists assess sprint running technique to increase understanding of current coaching and biomechanical practice leading to an identification of ways to improve coach-practitioner relationships. Australian sprint coaches (n=56) and international sport biomechanists (n=12) completed an online survey that asked questions relating to their knowledge of sprint running, current biomechanical-based practices and the coach-biomechanist relationship. A level of congruence was found in the two group`s understanding of sprinting technique with a number of similarities between aspects of the stance and swing phases especially around the instance of contact. There were key differences in the relative importance of the stance phase, arm movement and postural alignment of the body. The potential gaps in knowledge and practice suggested in this initial research create a foundation for further research into the coach-practitioner relationship and its overall effectiveness.